Impact of Noise on Investment and Price Behavior - Ahmad Raymond Trilaksana; Nugroho Agung Wijoyo (Dinasti International Journal of Management Science, 2022)
This study aims to determine the impact of the noise phenomenon on investment and price behavior. The research was conducted by means of a literature study, namely by reviewing the concepts and theories used based on the available literature, especially from published articles, journals and scientific studies. Based on the research results, noise has a significant influence on investment decision making for stock investors, which means that the higher the noise, the more frequent investment decisions will be made. The concept and theory which states that the possibility of noise is less for large companies than small companies is not proven valid and consistent.